Potential Renal Effects of Cigarette Smoking in the Diabetic State-A review - Swarup Kumar Kundu; Badhan Roy Tanny (Turkish Journal of Agriculture: Food Science and Technology)
Diabetes is an alarming global systemic metabolic disorder that can pose a major threat to patients. The serious consequences of cigarette smoking on the diabetic kidney are not well known among people in different countries. According to different studies, smoking enhances albuminuria in diabetic patients. On the other hand, urinary albumin is a sensitive indicator of glomerular injury. The abnormal trans-glomerular passage of albumin may be seen due to increased permeability of the glomerular capillary wall and their subsequent impaired reabsorption by the epithelial cells of the proximal tubule. Smoking with hyperglycemia increases lipid accumulation and oxidative stress, which mainly up-regulates TGF-β, accumulates AGEs, reduces nitric oxide production, and eventually causes glomerular basement membrane thickening and mesangial expansion that results in the development of glomerulosclerosis and nephropathy. The complex interaction between cigarette smoking and diabetic mellitus poses multiple challenges for researchers, physicians, and patients. Therefore, the present review article aims to find out the feasible consequences for the kidney of a diabetic patient due to the habit of cigarette smoking which may be useful for academicians and researchers in the future.